Relationships between the Parity and Pelvimetry of Egyptian Buffalo Cows: Prediction of Dystocia and Estimation of Age - Sary, Ramadan G.; Abdelrahman, Hisham A.; Mohamed, Ragab H.; Hussien, Ahmed M.; Hussein, Hassan A.; Khalil, Karim M. (Journal of Buffalo Science, 2022)
Background: The current study aimed to determine the most strongly correlated variable of pelvimetry with the parity in our native breed Egyptian buffaloes. Methods: The study was conducted on 36 female buffaloes (nullipara, n=14, primipara n=6 and pluripara, n=16 with 2-4 births) aged between <15 months, n=15 and 65 months, n=21. The internal and external pelvic measurements were obtained using the rice pelvimeter and Freeman’s measuring tape. Results: Strong positive linear relationships were found for the distance between ischiatic tuberosities and the distance between sacral tubercles with the correlation coefficients of 0.64 and 0.62, respectively. The conjugate diameter increased progressively with the age and number of births, with a correlation coefficient of 0.96. The pelvic area had a very strong positive linear relationship with a correlation coefficient of 0.89. The linear combination of the predictor variable (conjugate diameter), to predict the number of birth was developed successfully. Conclusion: The strong relationship between the conjugate diameter and the number of births could be employed to predict the dystocia and estimate the age of female buffalo. Furthermore, these findings could be aid paleontologists in studying buffalo fossils.